The effect of CO2-fixing steel slag powder on the flowability of cement-based materials - Rui, Yafeng; Huang, Tianyong; Jiao, Yaru (Materials today communications, 2025)
Steel slag is the industrial solid waste generated by steel mills, with a large amount of storage and difficult resource utilization. Moreover, industries such as steelmaking and cement production produce a large amount of CO2, which requires emission reduction and carbon sequestration. Therefore, using steel slag to store CO2 and then using it as building materials, it can achieve both the utilization of solid waste and exhaust gas, which is of great significance. This article focuses on the workability of CO2-fixing steel slag powder cement paste. The results show that although the activity of steel slag powder after carbonization is improved, it is not conducive to workability. The higher the CO2 sequestration amount, the lower the fluidity. However, it can alleviate the issue of delayed setting that arises from the incorporation of steel slag powder into cement. When the dosage is 30 %, the untreated steel slag powder can enhance the fluidity of cement, however, the distinction in fluidity between cement containing CO2-fixing steel slag powder and pure cement is insignificant. When the CO2-fixing steel slag powder dosage is further increased, the loss of fluidity is significant. The main reason for the change in fluidity is the increase in particle roughness. Even if the particle size distribution is adjusted, the loss of fluidity caused by roughness is still significant. [Display omitted]